Hiyal in Islamic finance: a recognition of genuine economic need or circumvention of Riba? - Syed, Ehsanullah Agha; Omar Mohamad, Mustafa (Emerald Group Publishing Ltd., 2017)
(singular of hiyal) is an Islamic juristic term which refers to the application of acumen and ingenuity to avoid hardship in one’s commitment to Islamic rulings. It has been used as a legal device in Islamic jurisprudence to actualize a legitimate objective. Particularly, it plays a significant role in financial engineering, as it alleviates financial predicaments with remedies. Design/methodology/approach – The study adopted qualitative method of research by using content analysis approach. Inductive reasoning is applied to drive legal provisions from Sharīʿah sources that would be used as basic principles to develop an objective measure for using hiyal in Islamic banking and finance. Findings – This study attempted to identify the distinctive features of legitimate hiyal for the purpose of developing a Sharīʿah framework. It is observed that a hīlah would be considered permissible in Islamic finance if it meets the prescribed criteria of (1) Sharīʿah objectives, (2) user’s motivation, (3) means, (4) benefit and (5) concessionary rules. This proposed framework may serve as an ‘objective measure’ that will determine whether a hīlah based financial engineering aims to actualize a genuine economic need or to circumvent the prohibition ofribā. Practical implications – The proposed standard of hiyal will enable Sharīʿah advisors, economists, financial engineer, legal experts and policy makers to develop comprehensive guidelines for using hiyal in Islamic financial engineering. Originality/value – Islamic financial institutions rely heavily on hiyal to operate in a predominant conventional financial system. The application of these legal stratagems in Islamic finance has been the center of an intense debate between Islamic economists and jurists. The former argues that over-reliance on hiyal not only divorces morality from technicality but also defeats the noble purposes of Islamic economics. This paper provides a synthesis of the diverse views on the subject to facilitate a minimum level of convergence among scholars on the permissibility of hiyal.